The Reference Genome of the Halophytic Plant Eutrema salsugineum - Yang, Ruolin; Jarvis, David J.; Chen, Hao; Beilstein, Mark; Grimwood, Jane; Jenkins, Jerry; Shu, ShengQiang; Prochnik, Simon; Xin, Mingming; Ma, Chuang; Schmutz, Jeremy; Wing, Rod A.; et al. (Frontiers in Plant Science, 2013)
A halophyte refers to a plant that can naturally tolerate high concentrations of salt in the soil, and its tolerance to salt stress may occur through various evolutionary and molecular mechanisms. Eutrema salsugineum is one of the halophytic species in the Brassicaceae family that can naturally tolerate multiple types of abiotic stresses that typically limit crop productivity, such as extreme salinity and cold. It has been widely used as a laboratorial model for stress biology research in plants. Here, we present the reference genome sequence (241 Mb) of E. salsugineum at 8x coverage sequenced by traditional Sanger sequencing-based approach with comparison to its close relative Arabidopsis thaliana. The E. salsugineum genome contains 26,531 protein-coding genes and 51.4% of its genome is composed of repetitive sequences that mostly reside in pericentromeric regions. Comparative analyses of the genome structures, protein-coding genes, microRNAs, stress-related pathways and estimated translation efficiency of proteins between E. salsugineum and A. thaliana suggest adaptation of halophyte to environmental stresses may occur via a global network adjustment of multiple regulatory mechanisms. The E. salsugineum genome provides a resource to identify naturally occurring genetic alterations contributing to the adaptation of the halophyte plants to salinity might be bioengineered in related crop species.